RETRACTED: Clinical observation of a patient diagnosed with Crohn's disease during pregnancy - I. I. Fazlyeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
RETRACTED ARTICLEWe present the clinical case of patient Z., 31 years, old with exacerbation of Crohn's disease during pregnancy. Although treatment was given, the pregnancy ended in stillbirth (29 weeks). The degree of activity of the disease determines the occurrence of complications during pregnancy. That is why pre-pregnancy preparation is necessary, especially when the disease is in remission.